Bringing the jellyfish home: environmental consciousness and 'sense of wonder' in young children's encounters with natural landscapes and places. Issue 8 (16th November 2016) - Jørgensen, Kari-Anne
Abstract : The over-arching aim of this study was to elucidate and interpret topics that are relevant to how we understand children's experiences and creation of meaning in natural landscapes and places within these landscapes. Following two nature-kindergarten groups regularly over ten months, the data for this ethnographic study consist of constructed narratives and narrative maps. Key topics relate to children's multi-sensory experiences and the development of environmental consciousness, and their 'sense of wonder' as a driving force for exploration, interpretation and creation of meaning. Implications of the study for discourses of environmental education in the early years and local practices of taking children into nature are also discussed.